1984
DOI: 10.1007/bf01935807
|View full text |Cite
|
Sign up to set email alerts
|

Local myocardial perfusion and epicardial NADH-fluorescence after coronary artery ligation in the isolated guinea pig heart

Abstract: In Langendorff-perfused guinea pig hearts, local myocardial perfusion was evaluated by analysis of FITC-dextran-150 elution kinetics after bolus injection. Locally estimated half-times of the monoexponential elution curves showed good correlation with global undisturbed coronary flow. After ligation of the left anterior descending coronary artery indicator transit kinetics in the ischemic area were only slightly affected (increase of t/2 by 30 +/- 19%), indicating a residual flow of 80% to the ligated area. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The guinea pig has a well-characterized autonomic neural phenotype (27,41) and has been successfully used to model ventricular fibrillation (18). However, guinea pigs have considerable cardiac arterial collateralization (39,45), and evidence has been presented that the guinea pig is impossible to infarct with a single coronary artery ligation (39), although others report variable success with this approach (30). For this reason, the arterial supply of the anterior left ventricle was ligated in four separate locations.…”
Section: Methodsmentioning
confidence: 99%
“…The guinea pig has a well-characterized autonomic neural phenotype (27,41) and has been successfully used to model ventricular fibrillation (18). However, guinea pigs have considerable cardiac arterial collateralization (39,45), and evidence has been presented that the guinea pig is impossible to infarct with a single coronary artery ligation (39), although others report variable success with this approach (30). For this reason, the arterial supply of the anterior left ventricle was ligated in four separate locations.…”
Section: Methodsmentioning
confidence: 99%
“…Some previous studies demonstrated that tying a single vessel off for a few days to weeks did not cause myocardial infarction in guinea pig hearts (14,15). However, other researchers showed that LCA ligation in guinea pigs resulted in infarction within 3 days of surgery (16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…Preparation of guinea pig hearts according to Langendorff. Hearts of adult guinea pigs were prepared as previously described (16). Briefly, the guinea pigs were heparinized (1,000 IU heparin/kg), and the hearts were excised.…”
Section: Calibration Of the No Electrodementioning
confidence: 99%